Source of Household Drinking Water and Diarrhoea among Children Under Five Years in Ghana - Dekoleadenu, D.J. (My University, 2015)
Safe drinking water is a basic need for good health as well as for human and economic development. Diarrhoea kills more than HIV and AIDS, and malaria combined. Diarrhoea kills about two million people especially children under five each year. The study investigates the relationship between source of household drinking water and diarrhoea incidence among children under five years in Ghana. A sample of 2,728 women who had given birth in the last five years preceding the survey was drawn from the children‟s file of the 2008 Ghana Demographic and Health Survey. Selected demographic characteristics of the mother and children under five years were used in the analysis. The study adopts quantitative analysis employing binary logistic regression methods. The results show that type of place of residence, age of the under-five children and household wealth quintile were strong predictors of diarrhoea incidence among children under five years of age in Ghana. However, type of toilet facility and source of household drinking water were not statistically significant predictors of under-five diarrhoea incidence. This may be due to the fact that water handling processes from the source to the point of use in households were not considered in the analysis because of lack of data. The study recommends among other things that programmes such as Livelihood Empowerment Against Poverty(LEAP) aimed at reducing poverty should be enhanced to enable more households have the means to be able to take care of their infants by providing them with good drinking water. Further studies should also consider including information on the process of handling water from the source to the point of use in the household which this study could not include for lack of data.
Thesis(MA)- University Of Ghana,2015
Keywords: Household; Drinking Water; Diarrhoea; Children; Ghana